Holothurin of some Philippine Holothurians and its hemolytic activity - Pocsidio, Glorina N. (1983)
Four Philippine holothurian species namely Holothuria fuscocinerea Jaeger, Holothuria pulla Selenka, Actinophyga lecanora Jaeger, and Opheodesoma grisea semper were studied for their holothurin extraction yields, hemolytic potency of the toxin, and some nutrient contents after holothurin extraction. On dry weight basis, holothium yields were for H. fuscocinerea, 1.74% H. pulla, 1.64% A, lecanova, 1.24% and O. grisea. ).89%. On fresh weight basis, holothurin yields were for H. fuscocinera, 0-27%, H. pulla, 0.14%, A. lecabova, 0.10% O. grisea, 0.09%. The least concentrations at which hemolysis was observed with holothurin in 2% human red blood cell suspension were for A. lecanora, 0.060% mg/ml, H. pulla, 0.060 mg/ml H fuscocinera, 0.015 mg/ml and O. grisea, 4 mg/ml. Aqueous extract of the cuvierian tubules of H. pulla was active at tle least concentration of 1 mg/ml. The C50 values or concentrations for 50% hemolysis in undiluted human blood are: H. fuscocinerea, 0.15 mg/ml, H. pulla, 0.60% mg/ml and A. lecanora 0.71 mg/ml which gave the order of hemolytic potency as follows: H fuscocinerea> H pulla> A lecanora. The dried body walls after holothurin extraction contained protein in A. lecanora, the dried body walls after holothurin extraction contained protein A. lecanora of 11.0% H pulla 65.3% and H. fuscocinerea 45.6% and high levels of calcium, phosphorous and iron in three species.